2017
DOI: 10.1177/1469066717730705
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of doubtful cases of leucine and isoleucine discrimination in mass spectrometric peptide sequencing by electron-transfer and higher-energy collision dissociation-based method

Abstract: Electron-transfer dissociation (ETD) and electron-transfer and higher-energy collision dissociation (EThcD) spectra of short tryptic peptides with leucine/isoleucine residues in neighboring positions demonstrate intensive w-ions. On the contrary, u-ions possess very low intensities (if present at all). Therefore radical site migration is negligible in the applied conditions while ETD (EThcD) spectra allow for the reliable discrimination of the isomeric residues in the sequencing process. The presence of a frag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…One valuable nontraditional application of ETD is for differentiating peptide isomers and isomeric residues . Lebedev et al and Xiao et al both recently described methods to perform HCD on z • -type generated from ETD to create diagnostic w-ions for distinguishing leucine and isoleucine residues in peptides. , Lebedev and co-workers further extended this study to EThcD methods for more globally applicable leucine/isoleucine discrimination, although they also described limitations and considerations when using these approaches . Lyon et al recently showed that ETD reactions can identify peptide isomers through a strategy that leverages hemolytic cleavage of carbon–iodine bonds that drives radical directed dissociation upon supplemental activation .…”
Section: Other Uses Of Etd and Related Ion–ion Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One valuable nontraditional application of ETD is for differentiating peptide isomers and isomeric residues . Lebedev et al and Xiao et al both recently described methods to perform HCD on z • -type generated from ETD to create diagnostic w-ions for distinguishing leucine and isoleucine residues in peptides. , Lebedev and co-workers further extended this study to EThcD methods for more globally applicable leucine/isoleucine discrimination, although they also described limitations and considerations when using these approaches . Lyon et al recently showed that ETD reactions can identify peptide isomers through a strategy that leverages hemolytic cleavage of carbon–iodine bonds that drives radical directed dissociation upon supplemental activation .…”
Section: Other Uses Of Etd and Related Ion–ion Reactionsmentioning
confidence: 99%
“… 289 , 290 Lebedev and co-workers further extended this study to EThcD methods for more globally applicable leucine/isoleucine discrimination, 291 although they also described limitations and considerations when using these approaches. 292 Lyon et al recently showed that ETD reactions can identify peptide isomers through a strategy that leverages hemolytic cleavage of carbon–iodine bonds that drives radical directed dissociation upon supplemental activation. 293 Additionally, Turacek and colleagues have used radical product ions, created via ETD, to extensively study structure and ion chemistry of peptides with a variety of approaches for theoretical and analytical purposes.…”
Section: Other Uses Of Etd and Related Ion–ion Reactionsmentioning
confidence: 99%
“…21,22 Moreover, EThcD has been shown to generate w ions which allow differentiation between leucine and isoleucine. 26,27 ETD has also been applied for the characterization of immunopeptides containing post-translational modifications (PTMs), which are not successfully identified by HCD. 24,25 While these methods have been promising, ETD and EThcD remain limited in their ability to characterize a broad spectrum of immunopeptides owing to the charge state dependence of these methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Owing to the broad importance of immunotherapies, mass spectrometry-based immunopeptidomics has been a growing field for the past 30 years . Peptides are commonly characterized using collisionally activated dissociation (CAD) or higher-energy collisional dissociation (HCD). , Electron transfer dissociation (ETD) as well as the hybrid method electron-transfer/higher energy collisional dissociation (EThcD) have also been explored for analysis of immunopeptides. EThcD methods have been shown to increase the number of unique peptide matches when combined with CAD. , Moreover, EThcD has been shown to generate w ions which allow differentiation between leucine and isoleucine. , ETD has also been applied for the characterization of immunopeptides containing post-translational modifications (PTMs), which are not successfully identified by HCD. , While these methods have been promising, ETD and EThcD remain limited in their ability to characterize a broad spectrum of immunopeptides owing to the charge state dependence of these methods. ETD and EThcD exhibit their best performance metrics in the identification of longer and more highly charged immunopeptides …”
Section: Introductionmentioning
confidence: 99%